Perfecting the union national and state authority in the US Constitution - Edling, Max M. (Oxford University Press, 2019)
Habitually interpreted as the fundamental law of the American republic, the US Constitution was in fact designed as an instrument of union between thirteen American republics and as a form of government for their common central government. It offered an organizational solution to the security concerns of the newly independent American states. Confederation was an established means for weak states to maintain their independence by joining in union to manage relations with the outside world from a position of strength. Confederation also transformed the immediate international environment by turning neighboring states from potential enemies into sister states in a common union or peace pact. The US Constitution profoundly altered the structure of the American union and made the federal government more effective than under the defunct Articles of Confederation. But it did not transform the fundamental purpose of the federal union, which remained the management of relations between the American states, on the one hand, and between the American states and foreign powers, on the other hand. As had been the case under the articles, the states regulated the social, economic, and civic life of their citizens and inhabitants with only limited supervision and control from the federal government. Interpreting the Constitution as an instrument of union has important implications for our understanding of the American founding. The Constitution mattered much more to the international than to the domestic history of the United States. Its importance to the latter was dwarfed by that of state constitutions and legislation"--